2017
DOI: 10.1186/s12966-016-0436-0
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour change techniques targeting both diet and physical activity in type 2 diabetes: A systematic review and meta-analysis

Abstract: BackgroundChanging diet and physical activity behaviour is one of the cornerstones of type 2 diabetes treatment, but changing behaviour is challenging. The objective of this study was to identify behaviour change techniques (BCTs) and intervention features of dietary and physical activity interventions for patients with type 2 diabetes that are associated with changes in HbA1c and body weight.MethodsWe performed a systematic review of papers published between 1975–2015 describing randomised controlled trials (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
251
2
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 268 publications
(285 citation statements)
references
References 88 publications
(134 reference statements)
24
251
2
8
Order By: Relevance
“…Our findings might suggest that higher frequency and greater number of contacts are associated with greater reductions in HbA 1c which is consistent with our previous systematic review of combined diet and physical activity interventions (8), although, this may arise from more intervention content being delivered. However, we cannot be sure because fidelity was so poorly reported in almost all categories and in all studies apart from one subcategory of 'monitoring and improving enactment of treatment skills' where 68.5% of studies reported use of fidelity.…”
Section: Moderator Analysis Of Intervention Featuressupporting
confidence: 91%
“…Our findings might suggest that higher frequency and greater number of contacts are associated with greater reductions in HbA 1c which is consistent with our previous systematic review of combined diet and physical activity interventions (8), although, this may arise from more intervention content being delivered. However, we cannot be sure because fidelity was so poorly reported in almost all categories and in all studies apart from one subcategory of 'monitoring and improving enactment of treatment skills' where 68.5% of studies reported use of fidelity.…”
Section: Moderator Analysis Of Intervention Featuressupporting
confidence: 91%
“…Of the remaining 6,173 articles, the titles and abstracts were screened for eligibility and 141 full texts were obtained for a full assessment. Nine reviews met all criteria (Alageel, Gulliford, McDermott, & Wright, ; Avery et al ., ; Cheng et al ., ; Cradock et al ., ; Dombrowski, Sniehotta, Avenell, & Coyne, ; Goodwin, Ostuzzi, Khan, Hotopf, & Moss‐Morris, ; Huttunen‐Lenz, Song, & Poland, ; Lara, Evans, et al ., ; Samdal, Eide, Barth, Williams, & Meland, ). In total, 132 texts were excluded (see Figure and Appendix S4 for excluded papers).…”
Section: Resultsmentioning
confidence: 99%
“…Systematic reviews in other health contexts suggest that use of BCTs does influence intervention outcomes, although not always positively . Varying combinations of BCTs (action planning, instructions, demonstration, behavioural practice, self‐monitoring, feedback, risk communication, social support, and graded tasks) were associated with positive outcomes in reviews of physical activity and dietary interventions across heterogeneous populations . However, in some reviews, goal setting, self‐monitoring, graded tasks, and social comparison were associated with poorer outcomes .…”
Section: Discussionmentioning
confidence: 99%